Lectotypifications of some Smithia (Fabaceae) occurring in India - Singh, Rajeev Kumar (Phytotaxa, 2016)
Fourteen binomials of eleven recognized species of Smithia are lectotypified: Smithia bigemina, S. blanda, S. blanda var. humilis, S. capitata, S. ciliata, S. dichotoma, S. gracilis, S. grandis, S. hirsuta, S. purpurea, S. pycnantha, S. paniculata, S. racemosa and S. setulosa.